8(k+11)-6k=9

Simple and best practice solution for 8(k+11)-6k=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(k+11)-6k=9 equation:


Simplifying
8(k + 11) + -6k = 9

Reorder the terms:
8(11 + k) + -6k = 9
(11 * 8 + k * 8) + -6k = 9
(88 + 8k) + -6k = 9

Combine like terms: 8k + -6k = 2k
88 + 2k = 9

Solving
88 + 2k = 9

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-88' to each side of the equation.
88 + -88 + 2k = 9 + -88

Combine like terms: 88 + -88 = 0
0 + 2k = 9 + -88
2k = 9 + -88

Combine like terms: 9 + -88 = -79
2k = -79

Divide each side by '2'.
k = -39.5

Simplifying
k = -39.5

See similar equations:

| 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 | | 15-2x=-19 | | .11x-.03(40000-x)=760 | | 5d+11=8d-7 | | 3x-2y+5y-8x= | | -2(x-5)-3x=120 | | (57/2)x=26.8 | | -2.3-5x-4.1-3x=-7x+1.6 | | 2(3m-4)=8m-11 | | -2(-2)+4(4)=8 | | -3(2x+4-3-6x)-2=10x | | i+i+1+i+2=228 | | -5/2-1/4 | | .04(2-q)=0.2(q+7) | | 2xy=8+5y | | 4x+40=-24 | | -3=-32t-1 | | -5/2*-6 | | 35x-9=23x+90 | | s+3/1/2s+20=74 | | 2(x-4)+8=3x |

Equations solver categories